Biomass production in mixed short rotation coppice with poplar‐hybrids (Populus spp.) and black locust (Robinia pseudoacacia L.) - Jessica Rebola‐Lichtenberg (Wiley, 2021)
Abstract Short rotation coppice plays an important role for biomass production. Mixing fast‐growing tree species in short rotation coppices may lead to overyielding if the species have complementarity traits. The goal of this study is to analyze biomass yield of eight different poplar hybrids and black locust in mixed short rotation coppice after a rotation of 5 years. Pure and mixed stands were established at two sites of contrasting fertility as a low‐input system. After collecting a sample of trees for the data set, we fitted allometric equations to estimate the overall biomass of the stands. All poplar genotypes showed lower performance in mixtures with black locust, whereas the latter profited from the mixture. In contrast to our expectations, poplars had no advantages from black locust's nitrogen enrichment of the soil. Instead, the dominance and competitiveness of black locust drove to poorer performance of all eight poplar genotypes across both sites. Mixing fast‐growing tree species in short rotation coppices may lead to overyielding if the species have complementarity traits. The goal of this study is to analyze biomass yield of eight different poplar hybrids and black locust in mixed short rotation coppice after a rotation of 5 years. While black locusts profited from mixed cropping, poplars had no advantaged performance. The dominance and competitiveness of black locust drove to poorer performance of all eight poplar genotypes.